Tinjauan Sosiologi Ekonomi Terhadap Perilaku Konsumsi Masyarakat Kota Makassar Pada Pasar Virtual - Andi Faisal Anwar; Idris Parakkasi; Bahrul Ulum Rusydi (AL-FALAH : Journal of Islamic Economics, 2018)
This study aims to analyze the behavior of public consumption, the factors that encourage people to transact in the virtual market, and forecasting the type of the market in the future related by consumption behavior. Therefore, the analytical method used is descriptive statistical analysis. The results showed that in terms of characteristics of people who spend in the virtual market dominated by women, high school educated, and having aged between 21-30 years, sources of information through social media, and the type of goods is a fashion product. In terms of consumer behavior and the value of goods, generally consumers still doubt on the quality of goods sold in the virtual market. The reasons of shoppings are efficiency and effectiveness as well as availability of new products. Furthermore, in terms of consumption behavior and hypereality, people tend to browse despite the desire to buy goods quite low, consumer exposure in non-virtual market will decrease in stead of in the virtual market, and then some people still doubt the level of trust and security transact in the virtual market. Religious values are essential to improving people's morale in exploiting virtual markets